2003
DOI: 10.1055/s-2003-38683
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Dithionite-InitiatedCoupling of 1-Bromo-1-chloro-2,2,2-trifluoro­ethane withPyrroles: A New, Convenient and Economical Synthesis of 5-(Trifluoromethyl)dipyrromethanes

Abstract: Sodium dithionite-initiated reactions of pyrrole and 1methylpyrrole with 1-bromo-1-chloro-2,2,2-ethane in an acetonitrile-water mixture provide the respective 5-(trifluoromethyl)dipyrromethanes 1 and 3 as main products in 40-58% isolated yields and of high purity. Small amounts of tripyrranes 2 and 4 are also formed and could be isolated from the reaction mixtures. 1-Methyl-2,5-bis[2,2,2-trifluoro-1-(1-methyl-2-pyrrolo)ethyl]pyrrole (4) Mp 194-196 °C. EI-MS: m/z (%) = 403 (58, M + ), 334 [100, (M -CF 3 ) + ], … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 7 publications
2
23
0
Order By: Relevance
“…The reactions proceeded at similar rates affording similar, high yields of products as with an equivalent amount of the initiator. There are only two papers [8,9] prior to the present work, reporting the use of a low ratio of the initiator to a perhaloalkane. Low ratio of the initiator to CF 3 CHClBr suggests a free radical chain mechanism, possibly as depicted in Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactions proceeded at similar rates affording similar, high yields of products as with an equivalent amount of the initiator. There are only two papers [8,9] prior to the present work, reporting the use of a low ratio of the initiator to a perhaloalkane. Low ratio of the initiator to CF 3 CHClBr suggests a free radical chain mechanism, possibly as depicted in Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
“…In the preceding papers [6][7][8], we reported that sulfinatodehalogenation procedure could be applied to 1-bromo-1-chloro-2,2,2-trifluoroethane, commercially available as Halothane 1 (inhalation anaesthetic), to generate CF 3 CHCl . radicals which readily reacted with vinyl ethers [6,7] and with pyrroles [8].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the large upfield shift of H(1) may be ascribed to the local diatropic ring current effect of the pyrrole C, which is close to H(1) with a distance of 2.57 . In contrast to the quantitative and reversible redox interconversions between [24]-and [22]NFP 5 [23,24] bearing meso-pentafluorophenyl substituents, oxidation of 3 to its [22]NFP 5 counterpart was found to be difficult even with DDQ or MnO 2 under forcing conditions.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…meso-Trifluoromethyl-substituted dipyrromethane [22] 10 was treated with four equivalents of TFAA in THF at À20 8C to give 2-trifluoroacetyl-6-trifluoromethyldipyrro-A C H T U N G T R E N N U N G methane in 82-88 % yield, which was quantitatively reduced with NaBH 4 to its carbinol 11. Self-condensation reaction of 11 with one equivalent of HCl in refluxing CH 2 Cl 2 provided a series of meso-trifluoromethyl-substituted expanded porphyrins bearing an even number of regularly arranged pyrrole rings and methine carbon atoms (2 1-3 %, 4 8-10 %, 6 1 %, and 7~1 %, Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…In our laboratory, it has been found that the Na 2 S 2 O 4 /acetonitrile/H 2 O system is also able to promote addition of polyhaloalkanes, i.e.1-bromo-1-chloro-2,2,2-trifluoroethane (Halothane 1 ) [9][10][11][12] and dibromodifluoromethane [13,14] to various electron-rich unsaturated compounds but most attempts to alkylate aromatic and heteroaromatic compounds with these reagents were unsuccessful. The only successful exceptions were reactions of 1-bromo-1-chloro-2,2,2-trifluoroethane with 1,3,5-trimethoxybenzene and with pyrroles, which resulted in coupling of one molecule of CF 3 CHClBr with two molecules of the aromatic compound to give, respectively, trifluoromethyl-bis(2,4,6-trimethoxyphenyl)methane [15] and 5-(trifluoromethyl)-dipyrromethanes [16] in a 38-50% yields. In those reactions both, Br and Cl atoms of CF 3 CHClBr were replaced with an aromatic moiety.…”
Section: Introductionmentioning
confidence: 99%